2021
DOI: 10.1007/s00018-021-04062-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term caffeine treatment of Alzheimer mouse models ameliorates behavioural deficits and neuron loss and promotes cellular and molecular markers of neurogenesis

Abstract: Epidemiological studies indicate that the consumption of caffeine, the most commonly ingested psychoactive substance found in coffee, tea or soft drinks, reduces the risk of developing Alzheimer’s disease (AD). Previous treatment studies with transgenic AD mouse models reported a reduced amyloid plaque load and an amelioration of behavioral deficits. It has been further shown that moderate doses of caffeine have the potential to attenuate the health burden in preclinical mouse models of a variety of brain diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 83 publications
4
31
0
Order By: Relevance
“…Likewise, neuron population assessed by the NeuN/DAPI ratio was reduced after GM-IVH in the cortex and the SVZ from mice with GM-IVH, and Caf treatment counterbalanced this situation. These data support the capacity of Caf to limit neuronal loss, in line with previous studies showing that Caf may promote neuron survival after an hypoxic situation (Li et al, 2019;Soontarapornchai et al, 2021) or other insults (Stazi et al, 2021;Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, neuron population assessed by the NeuN/DAPI ratio was reduced after GM-IVH in the cortex and the SVZ from mice with GM-IVH, and Caf treatment counterbalanced this situation. These data support the capacity of Caf to limit neuronal loss, in line with previous studies showing that Caf may promote neuron survival after an hypoxic situation (Li et al, 2019;Soontarapornchai et al, 2021) or other insults (Stazi et al, 2021;Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, Caf treatment at the highest dose (20 mg/kg/day) successfully restored neurogenesis impairment, suggesting that Caf effects might not be circumscribed to limiting neuronal loss, but it may also promote neurogenesis. Whereas some studies have shown that Caf may compromise proliferation of human hippocampal progenitor cells (Houghton et al, 2020), neurogenesis seems to improve after Caf treatment in different animal models (Mao et al, 2020;Stazi et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Mice were housed in groups of 4–5 in all conditions to ensure social interactions; food and water were provided ad libitum . Data from vehicle- and caffeine-treated SH groups have been partially published in a previous study [ 63 ], where they served as control groups within a larger set of experiments to minimize experimental animal numbers. All animals were handled according to the German guidelines for animal care and all experiments have been approved by the local animal care and use committee (Landesamt für Verbraucherschutz und Lebensmittelsicherheit (LAVES), Lower Saxony, Approval number 17/2701).…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial evidence that the regular consumption of moderate caffeine attenuates memory deficits [169]. This is most evident when considering the beneficial effects of caffeine intake in different models of Alzheimer's disease such as in transgenic models leading to the over-function of the amyloid cascade [170,171] or tau [172], as well as in models of sporadic Alzheimer's disease [161]. This prevention of memory deficits by caffeine is mimicked by the pharmacological or genetic blockade of A2AR [133,135,[172][173][174].…”
Section: Cognitive Deficitsmentioning
confidence: 99%